2017
DOI: 10.1093/scan/nsx070
|View full text |Cite
|
Sign up to set email alerts
|

White matter correlates of psychopathic traits in a female community sample

Abstract: Psychopathy comprises interpersonal, affective, lifestyle and antisocial facets that vary dimensionally in the population and are associated with criminal offending and adverse psychosocial outcomes. Evidence associating these facets with white matter microstructure of the uncinate fasciculus and the cingulum tracts is inconsistent and derives principally from studies of male offenders. In a sample of 99 young women presenting a range of scores on the Psychopathy Checklist: Screening Version, we used Diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 89 publications
(129 reference statements)
1
12
0
Order By: Relevance
“…These findings were in general attributed to the interpersonalaffective dimensions (85,89,124), but also to a lesser extent to lifestyle-antisocial dimensions (85). Moreover, increased radial diffusivity (RD) in the uncinate fasciculus correlated with the interpersonal dimension of psychopathy (16).…”
Section: Diffusion Tensor Mri Findings In Psychopathymentioning
confidence: 98%
See 2 more Smart Citations
“…These findings were in general attributed to the interpersonalaffective dimensions (85,89,124), but also to a lesser extent to lifestyle-antisocial dimensions (85). Moreover, increased radial diffusivity (RD) in the uncinate fasciculus correlated with the interpersonal dimension of psychopathy (16).…”
Section: Diffusion Tensor Mri Findings In Psychopathymentioning
confidence: 98%
“…The integrity of white matter structures appeared to play a pivotal role in psychopathy. Several studies showed reduced fractional anisotropy (FA) in the uncinate fasciculus on the right side (73,87,89) and bilaterally (16,85,88). These findings were in general attributed to the interpersonalaffective dimensions (85,89,124), but also to a lesser extent to lifestyle-antisocial dimensions (85).…”
Section: Diffusion Tensor Mri Findings In Psychopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Women were recruited from a longitudinal study of adolescents who consulted for substance misuse at a specialized clinic in Stockholm 73 76 . Thirty-nine ex-clients had been assessed at baseline, and 6, 12, 60 and 78 months later.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the shape and location of the UF (which intersects both with the inferior fronto-occipital tract in the OFC and the inferior longitudinal tract in the temporal pole), voxelwise methods that rely on inter-subject normalization, such as Tract-Based Spatial Statistics 87 used in our previous study, contrasting whole-brain white matter integrity between CD and healthy women 74 , are limited in their abilities to properly delineate the UF. Instead, whole-brain tractography and manual, virtual dissection was employed 76 . Preprocessed diffusion-weighted data were tensor-fitted in Diffusion Toolkit and whole-brain tractography performed using the interpolated streamline algorithm, an angle threshold of 34° and a standard FA interval of 0.2–1.…”
Section: Methodsmentioning
confidence: 99%